Choreographic Architectures: When Dancing Designs the Urban Environment (Itinera, 2023)
This paper aims to draw attention to the relationship between dance and architecture. After a historical and conceptual contextualisation, it sheds light on how the term choreography evolved its meaning along the twentieth century, indicating a dispositif for building a new ecology of the participative performance experience. In these terms, choreographic architectures can be recognised when in real and metaphysic spaces, movement strategies are planned to activate processes through which human dancing engages with the surrounding environment. This phenomenon is studied by comparing William Forsythe’s theory of the “choreographic object” with some installations performed in urban environments. Finally, to provide an enlarged vision of how a choreographic strategy can cooperate in building a performative ecology to regenerate the inhabiting contexts with the acting presences of socially empowered citizens, my analysis ends with the description of Asingeline and Garden State, two emblematic works by MaMaZa, a Frankfurt-based group of artists.